Class-switched Primary Cutaneous Marginal Zone Lymphomas Are Frequently IgG4-positive and Have Features Distinct From IgM-positive Cases. (October 2019) - Carlsen, Eric D.; Swerdlow, Steven H.; Cook, James R.; Gibson, Sarah E.
Abstract : Primary cutaneous marginal zone lymphoma (PCMZL) can be subdivided into 2 groups based on immunoglobulin (Ig) heavy chain usage: IgM-positive cases that constitute a less common and more T-helper type 1–driven process, and more common heavy chain class-switched cases that are predominantly T-helper type 2–driven. Although some report a significant IgG4-positive subset, others have found a much smaller proportion. To further evaluate the proportion of IgG4-positive PCMZL, to address whether IgG4-positive cases have any distinctive characteristics, and to assess whether additional features separating IgM-positive and class-switched cases could be identified, the clinicopathologic features of 26 PCMZL obtained from 19 patients were investigated. Twenty of 26 (77%) PCMZL were heavy chain class-switched (19 IgG-positive, 1 IgA-positive), including 9 that were IgG4-positive (35%). IgG4-positive and other class-switched PCMZL were morphologically similar. IgM-positive cases occurred in older individuals (median: 69 vs. 46.5 y; P =0.0001), more often involved the subcutis ( P =0.002), demonstrated plasma cells diffusely scattered versus at the periphery of the lymphoid infiltrate ( P =0.005), uniformly showed follicular colonization ( P =0.0001), contained more numerous B cells ( P =0.0004), and were more likely to have a T-cell CD4:CD8 ratio of <3:1 ( P =0.03). None of the IgM-positive PCMZL harbored a MYD88 L265P mutation. No significant differences in clinical outcome were documented. These results highlight the high frequency of IgG4-positive PCMZL, which are otherwise similar to other class-switched cases, provide additional evidence supporting the distinction between class-switched and IgM-positive cases, and emphasize the indolent nature of at least the class-switched PCMZL, which may warrant their categorization as a clonal chronic lymphoproliferative disorder.